THE EFFECT OF GIVING GAMAL LEAF BLOCK ON THE HEMATOLOGICAL PROFILE OF CATTLE EXPERIENCING ANESTRUS - Rahmadani, Resinta Delia; Samsuri; Wandia, I Nengah; Merdana, I Made; Sulabda, I Nyoman; Kendran, Anak Agung Sagung (Buletin Veteriner Udayana, 2024)
Anestrus is a condition in female animals that do not show symptoms of estrus for a long period of time. Anestrus in cows can cause physiological, environmental and management changes. Gamal leaves can be used as a source of protein for livestock. Mother cows experience fluctuating hematological changes, such as hemoglobinemia, erythropenia and leucocythemia. This study aims to determine the effect of gamal block on hemoglobin levels, total erythrocytes, hematocrit values ​​and total leukocytes in Bali cattle experiencing anestrus. This research used 6 anestrus Bali cattle selected using purposive sampling. The six cows were given gamal block treatment with a composition of 250 grams of gamal leaf simplicial, 200 ml propylene glycol and 4 grams of salt for 14 days. After that, a 2ml blood sample was taken via the jugular vein on day 0, day 10 and day 20. The results of the study obtained mean hemoglobin levels sequentially on days 0, 10 and 20, namely 8.98 ± 0.23 g/dL, 8.78 ± 0.23 g/dL, 8.26 ± 0, 23 g/dL. Total erythrocytes were 4.80±0.18 106/μL, 4.92±0.18 106/μL, 4.73±0.18106/μL respectively. Hematocrit values ​​were 29.53 ± 0.60 %, 28.23 ± 0.60 %, 26.64 ± 0.61 %, respectively. And total leukocytes were 7.21±0.27 103/μL, 7.56±0.27 103/μL, 6.63±0.27 103/μL respectively. The statistical results showed that giving gamal leaf blocks for 14 days did not affect hemoglobin levels, total erythrocytes, hematocrit values ​​and total leukocytes in Bali cattle experiencing anestrus.